2021
DOI: 10.1039/d1na00565k
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction-based photocatalytic nitrogen fixation: principles and current progress

Abstract: Nitrogen fixation is considered one of the grand challenges of the 21st century for achieving the ultimate vision of a green and sustainable future. It is crucial to develop and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 126 publications
(168 reference statements)
0
34
0
Order By: Relevance
“…The LSPR is mostly used to compensate for the weakness of semiconductor materials, such as doping metal nanoparticles in heterogeneous-structured photocatalysts, thus enhancing the photocatalytic activity of the catalysts using LSPR. 80 Recently, unique visible light LSPR absorption properties have been used to design photocatalytic nitrogen fixation systems. It was found that some semiconductor nanomaterials exhibit excellent LSPR absorption in the visible and nearinfrared light ranges and have more abundant means of modulation than metallic nanomaterials.…”
Section: Localized Surface Plasmon Resonance (Lspr)mentioning
confidence: 99%
“…The LSPR is mostly used to compensate for the weakness of semiconductor materials, such as doping metal nanoparticles in heterogeneous-structured photocatalysts, thus enhancing the photocatalytic activity of the catalysts using LSPR. 80 Recently, unique visible light LSPR absorption properties have been used to design photocatalytic nitrogen fixation systems. It was found that some semiconductor nanomaterials exhibit excellent LSPR absorption in the visible and nearinfrared light ranges and have more abundant means of modulation than metallic nanomaterials.…”
Section: Localized Surface Plasmon Resonance (Lspr)mentioning
confidence: 99%
“…The common methods are as follows: (1) Nessler's reagent; (2) indophenol blue method; (3) ion chromatography; (4) isotope labelling nuclear magnetic resonance (NMR). 104 Among the above methods, Nessler's reagent method has become the most widely used method in the determination of NH 3 due to its simple principle and easy operation. In a typical process, an alkaline solution of Nessler's reagent (K 2 HgI 4 ) reacts with NH 3 in the system to form a red-brown complex (Hg 2 ONH 2 I), which is detected by a characteristic absorption peak at 420 nm.…”
Section: Other Products Of Photocatalytic Nitrogen Fixationmentioning
confidence: 99%
“…The common methods are as follows: (1) Nessler's reagent; (2) indophenol blue method; (3) ion chromatography; (4) isotope labelling nuclear magnetic resonance (NMR). 104…”
Section: Other Products Of Photocatalytic Nitrogen Fixationmentioning
confidence: 99%
“…For example, frequent replacement of electrodes and membranes due to fouling increases the operational costs of EO and membrane filtration techniques, respectively [5]. Photocatalysis, in this regard, is currently considered the most sustainable method and has been employed in various applications such as pollutants removal, fuel generation, pathogen elimination, and nitrogen fixation [6][7][8]. A typical photocatalysis process requires only a suitable semiconductor photocatalyst, reaction medium and solar light irradiation as an energy input.…”
Section: Introductionmentioning
confidence: 99%